Proposal of a Novel Mooring System Using Three-Bifurcated Mooring Lines for Spar-Type Off-Shore Wind Turbines - Shi Liu; Yi Yang; Chengyuan Wang; Yuangang Tu; Zhenqing Liu (Energies, 2021)
Floating wind turbine vibration controlling becomes more and more important with the increase in wind turbine size. Thus, a novel three-bifurcated mooring system is proposed for Spar-type floating wind turbines. Compared with the original mooring system using three mooring lines, three-bifurcated sub-mooring-lines are added into the novel mooring system. Specifically, each three-bifurcated sub-mooring-line is first connected to a Spar-type platform using three fairleads, then it is connected to the anchor using the main mooring line. Six fairleads are involved in the proposed mooring system, theoretically resulting in larger overturning and torsional stiffness. For further improvement, a clump mass is attached onto the main mooring lines of the proposed mooring system. The wind turbine surge, pitch, and yaw movements under regular and irregular waves are calculated to quantitatively examine the mooring system performances. A recommended configuration for the proposed mooring system is presented: the three-bifurcated sub-mooring-line and main mooring line lengths should be (0.0166, 0.0111, 0.0166) and 0.9723 times the total mooring line length in the traditional mooring system. The proposed mooring system can at most reduce the wind turbine surge movement 37.15% and 54.5% when under regular and irregular waves, respectively, and can at most reduce the yaw movement 30.1% and 40% when under regular and irregular waves, respectively.